Comprehensive Evaluation of Green Construction in Building Projects Using an Integrated MCDM and Plithogenic Set Approach - Yuqian Liu; Xuan Yu; Shuangquan Zheng (Neutrosophic Sets and Systems)
Green construction aims to minimize the overall negative impact of the built environment on both human health and the environment by efficiently using energy, water, and other resources. It helps reduce waste, pollution, and environmental impact while enhancing worker productivity and protecting occupant health. This study introduces a multi-criteria decision-making (MCDM) approach to evaluate green construction in building projects. The MCDM approach is integrated into the plithogenic set framework to address uncertainty and vague information. The simple additive weighting (SAW) method is employed to rank the alternatives. Three experts evaluated nine criteria and eight alternatives to determine the criteria weights and rank the alternatives. Sensitivity analysis was conducted to assess the stability of the rankings, with results showing that the ranks of the alternatives remain stable under varying criteria weights.